Strategies to Improve Neonatal Intubation Safety by Preventing Endobronchial Placement of the Tracheal Tube-Literature Review and Experience at a Tertiary Center - Joaquim M. B. Pinheiro; Upender K. Munshi; Rehman Chowdhry (MDPI AG, 2023)
Unintended endobronchial placement is a common complication of neonatal tracheal intubation and a threat to patient safety, but it has received little attention towards decreasing its incidence and mitigating associated harms. We report on the key aspects of a long-term project in which we applied principles of patient safety to design and implement safeguards and establish a safety culture, aiming to decrease the rate of deep intubation (beyond T3) in neonates to <10%. Results from 5745 consecutive intubations revealed a 47% incidence of deep tube placement at baseline, which decreased to 10-15% after initial interventions and remained in the 9-20% range for the past 15 years; concurrently, rates of deep intubation at referring institutions have remained high. Root cause analyses revealed multiple contributing factors, so countermeasures specifically aimed at improving intubation safety should be applied before, during, and immediately after tube insertion. Extensive literature review, concordant with our experience, suggests that pre-specifying the expected tube depth before intubation is the most effective and simple intervention, although further research is needed to establish accurate and accepted standards for estimating the expected depth. Presently, team training on intubation safety, plus possible technological advances, offer additional options for safer neonatal intubations.